Iron oxide-functionalized carbon nanofilaments for hydrogen sulfide adsorption: The multiple roles of carbon. (December 2015) - Fauteux-Lefebvre, Clémence; Abatzoglou, Nicolas; Blais, Sonia; Braidy, Nadi; Hu, Yongfeng
Abstract: Iron-functionalized carbon nanofilaments (Fe–CNF) have been tested as sorbents for low-temperature (T) gas desulfurization. This patent-pending material has a high hydrogen sulfide (H2 S)-removal capacity while allowing for low-H2 S breakthrough at the exit gas. CNF were produced by a patented ethanol dry reforming process, then acid-treated prior to Fe functionalization through a wet impregnation-calcination protocol. Desulfurization tests were performed with 35- to 95-mg samples and gas flow of 500 ppm H2 S in helium. To understand the desulfurization process, fresh and used Fe–CNF were analyzed thoroughly by X-ray absorption near-edge spectroscopy and X-ray photoelectron spectroscopy. The results show that carbon (C) has 2 important roles in this Fe–CNF sorbent: it acts both as sulfur adsorbent and nanometric support which disperses Fe efficiently in oxide form, enhancing the H2 S capture rate and efficiency. As well, iron oxide has 2 roles in the sorbent: at low T (100 °C), it acts as adsorption catalyst for H2 S-dissociative oxidation, and at higher T (300 °C), it reacts with H2 S to form iron sulfide. At the higher T tested, sulfidation occurred in parallel with C adsorption.